217k views
3 votes
Which of the following is the result of expanding

Which of the following is the result of expanding-example-1
User Frank Luke
by
4.5k points

2 Answers

5 votes

Answer:

Correct option is the second option, B

User Jxy
by
5.7k points
4 votes

The given expression is 2x-3 .

So when x =1, we will get 2(1)-3 = 2-3 =-1

When x=2, we will get, 2(2) -3 = 4-3 =1

When x=3, we will get 2(3)-3 = 6-3=3

When x=4, we will get 2(4)-3 = 8-3=5

So the required result of the expansion is -1+1+3+5=8

Correct option is the second option .

User Jeno Laszlo
by
6.0k points